Retinopathy of Prematurity. Review - N. V. Popova; A. P. Goydin; O. L. Fabrikantov (Oftalʹmologiâ)
Retinopathy of prematurity (RP) is a complex pathology among prematurely born children, which requires a comprehensive approach, including both prevention of the development of more severe stages of the disease, leading to poor vision and irreversible loss of visual functions, and the organization of dispensary observation and rehabilitation. Modern organization of dispensary observation, which is based on a detailed study of the etiology, pathogenesis, as well as the interaction of local and systemic factors on visual functions, can significantly reduce the visual disability of children as a result of this disease.